1993
DOI: 10.1128/jb.175.12.3798-3811.1993
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Escherichia coli FIS protein in maintenance of bacteriophage mu lysogeny by the repressor: control of early transcription and inhibition of transposition

Abstract: The Escherichia coli FIS (factor for inversion stimulation) protein has been implicated in assisting bacteriophage Mu repressor, c, in maintaining the lysogenic state under certain conditions. In a fis strain, a temperature-inducible Mucts62 prophage is induced at lower temperatures than in a wild-type host (M. Betermier, V. Lefrere, C. Koch, R. Alazard, and M. Chandler, Mol. Microbiol. 3:459-468, 1989

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…Fis also stimulates DNA excision in the case of the -like phage HK022 but, in addition, serves to repress a DNA inversion event upon establishment of lysogeny which would otherwise yield defective lysogens (10). Increased stability of and Mu lysogens is also observed in the presence of Fis (3,5,6). Even transposition frequencies of transposon Tn5 and insertion sequence IS50 are found to be influenced by Fis (60).…”
mentioning
confidence: 75%
“…Fis also stimulates DNA excision in the case of the -like phage HK022 but, in addition, serves to repress a DNA inversion event upon establishment of lysogeny which would otherwise yield defective lysogens (10). Increased stability of and Mu lysogens is also observed in the presence of Fis (3,5,6). Even transposition frequencies of transposon Tn5 and insertion sequence IS50 are found to be influenced by Fis (60).…”
mentioning
confidence: 75%
“…as opposed to a direct effect on repressor synthesis (5). A general effect of a fis mutation on osmoregulation causing the increase in LacZ levels of the frg fusions is considered unlikely, since most of the frg fusions do not display increased expression levels upon a shift to high medium osmolarity in fis ϩ cells (49).…”
Section: Vol 177 1995 Genes Negatively Regulated By Fis 943mentioning
confidence: 99%
“…This hypothesis is supported by results of the DNase I footprinting experiment, which revealed that Fis binds to the left terminus of IS2 at nucleotide number 44-60 (Fig. The effect of Fis on DNA transposition has also been observed in Mu and Tn5 (Betermier et al, 1989;Weinreich & Reznikoff, 1992;Betermier et al, 1993;van Drunen et al, 1993). Because this is the À 10 region of the major IS2 promoter (Fig.…”
Section: Discussionmentioning
confidence: 68%